Linguistic comedy across contexts: Twain’s dialect, Leacock’s hyperbole, Narayan’s subtle irony - G. BANAZEER BANU: Dr.S.GUNASEKARAN (The Bioscan, 2025)
This research paper explores the nuanced deployment of linguistic strategies to generate humor in the select works of Mark Twain, Stephen Leacock, and R.K. Narayan. Situated within a cross- cultural framework, the study investigates how each writer crafts a unique comic vision through dialectal variation, hyperbolic expression, and understated irony. Drawing on representative texts—Twain’s The Celebrated Jumping Frog of Calaveras County and Adventures of Huckleberry Finn, Leacock’s Sunshine Sketches of a Little Town and Arcadian Adventures with the Idle Rich, and Narayan’s Malgudi Days and The Guide—the paper undertakes a comparative textual analysis to identify linguistic markers that produce comic effect. The study is structured into five sections. The introduction situates the authors within their respective cultural and literary traditions, emphasizing the centrality of language in their humor. The literature review outlines key theories of humor, such as incongruity, superiority, and relief, alongside relevant studies in stylistics and sociolinguistics. The methodology section adopts a qualitative approach using discourse analysis and pragmatic tools, including Gricean maxims and speech act theory. The analysis and discussion section examines how Twain’s use of regional dialect and idiomatic speech, Leacock’s satirical verbosity and comic inflation, and Narayan’s minimalist irony reflect cultural specificity while invoking universal laughter. The conclusion synthesizes these findings, arguing that linguistic comedy, though locally inflected, fosters transnational reader engagement and empathy.This paper contributes to humor studies, comparative literature, and stylistic analysis by foregrounding language as a powerful medium of comic expression across literary cultures.